Penerapan Model Pembelajaran Kooperatif Tipe Number Head Together (NHT) Untuk Meningkatkan Kerjasama Siswa Sekolah Dasar - Mertayasa, I Komang; Pustikayasa, I Made (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2024)
Education does not only focus on developing cognitive aspects, but also needs to be directed at improving affective aspects. Collaboration as a form of affective aspect of students needs to continue to be developed so that it will be able to produce people who have an understanding of the importance of working together and the other impacts it has. However, there is still a reluctance among students to complete assignments together, and even tend to do it independently, even though it is a group assignment. The importance of cooperation for students makes teachers gives pressure for emphasis on the cooperation aspect in classroom learning by implementing learning methods that lead to the development of cooperation skills, including by implementing the Number Heads Together (NHT) type cooperative model. Analysis of research data shows that the application of the NHT model in learning can increase student collaboration. This can be seen from the increase in the total average score from cycle I of 74, increasing to 82.5 in cycle II and being in the Very Good category.